Penerbitan karya pantun dan syair Cina Baba di Tanah Melayu - Ding , Choo Ming (Universiti Kebangsaan Malaysia, 2002)
Written in ‘baba Malay’ with many loan-words from the Chinese language, pantun, syair and dondang by the Malayian Chinese-baba are intriguing. They began publishing the referred-to-poetry in Malacca, Singapore and Penang in late 19th century after the printing technology and missionary education were introduced in the Malay World. The works by these authors, including Na Tien Piet and Siow Hay Yam, represent a very important and unique chapter in the history of modern Malay literature besides having great cultural, intellectualial and social values as they portray the life and views of the Chinese baba community, and their relationship with the Malays. However, until today, development and the dynamic growth of such literature, spanning over half a century (1890s-1940s), is alienated and at best treated as marginal literature in the history of Malay literature as it is perceived to lack literary prestige of literary works by Malay authors